Examining the state of infrastructure development in Sub-Saharan Africa (Journal of Economic Research & Business Administration, 2021)
Infrastructure services are not only crucial for enhancing the welfare of the people but to also fostereconomic growth and development. Despite these essential services, there is a glaring infrastructuregaps in Sub-Saharan Africa more than any other region in the world. In the light of this and measurementproblems associated with infrastructure development, it is therefore necessary to highlight the state ofinfrastructure development in SSA. This study examines the state of infrastructure development in SSAby considering 43 nations over the period of 2000 to 2018. Infrastructure development was proxied bythe composite infrastructure index which include both the physical and social infrastructure. The studyemployed Principal Components Analysis (PCA) in building the aggregate or composite index, anddescriptive statistics, stylized facts and correlation analysis were employed for the analysis of the data.Findings from this study reveal that infrastructural development has improved significantly in SSA for theperiod of study even though this is very low compare to the development attained in other regions of theworld, and most of the improvement are from physical infrastructure, most especially telecommunicationsector, and to a lesser degree, in health and water infrastructure. The study therefore recommendsthat stakeholders should engage in policies design that will improve infrastructure development in SSAmost especially for the low income countries as majority of them were found at the bottom of ranking.This will help in closing the wide gap of inequality in access to infrastructure services among the SSAcountries and other developing countries in other regions of the world.Key words: Infrastructure development, Composite Infrastructure Index, Principal ComponentsAnalysis, Physical and Social Infrastructure.